circRNA Expression Pattern and circRNA–miRNA–mRNA Network in HCs, HSCs, and KCs of Murine Liver After Echinococcus multilocularis Infection - Liu, Tingli; Wang, Liqun; Li, Hong; Li, Yanping; Chen, Guoliang; Pu, Guiting; Guo, Xiaola; Zheng, Yadong; Bai, Xue; Luo, Xuenong (Frontiers in Veterinary Science, 2022)
Caused by Echinococcus multilocularis (E. multilocularis), alveolar echinococcosis is reported every year around the world and severely threatens the safety of human beings and animals. However, the molecular interaction relationships between host and E. multilocularis still remains unclear. With multiple functions, circRNA plays a crucial role in regulating the development of a parasitic disease. With that in mind, the main purpose of this study was to reveal the circRNA expression profiles and circRNA–miRNA–mRNA network relationships in hepatocytes (HCs), hepatic stellate cells (HSCs), and Kupffer cells (KCs) of murine liver after E. multilocularis infection. After sequencing, 6,290 circRNAs were identified from 12 hepatic cell samples. Based on the subsequent analysis, 426 and 372 circRNAs were significantly different in HC expression at 2 and 3 months after E. multilocularis infection, and similar results were also demonstrated in HSCs (426 and 372 circRNAs) and KCs (429 and 331 circRNAs), respectively. Eight candidate circRNAs were randomly selected to identify the accuracy of the sequencing results by using qRT-PCR. Additionally, three circRNAs–miRNA–mRNA networks in HCs, HSCs, and KCs were constructed. Taken together, our study provided a systematic presentation of circRNAs in murine liver cells after E. multilocularis infection, and these networks are essential for research in circRNAs associated with E. multilocularis infection.